Comparative analysis of large language model and physician-generated responses in bariatric patient inquiries: assessing the accuracy and patient satisfaction - Vedder, Katharina; Blank, Susanne; Wilhelm, Tea; Fidan, Darick; Pachkiv, Ihor; Cao, Han; Weiß, Christel; Li, Chengpeng; Rung-Friebe, Marion; Reißfelder, Christoph; Otto, Mirko; Yang, Cui (Obesity surgery, 2025)
Large language models (LLMs) can generate human-like, empathetic responses within seconds. Their potential in terms of comprehensibility, empathy, and completeness to support physician-patient communication in bariatric surgery care needs to be evaluated.
Online veröffentlicht: 1. August 2025; Artikelversion: 1. August 2025
Gesehen am 19.11.2025